Molecular Characteristics of Iraqi Lactobacillus plantarum Isolates and Evaluate its Natural Bacteriocin(plantaricins) Antimicrbial Activity against Pathogenic Bacteria - Khadeeja S. Madhi; Mohammed H. Khudr; Rasha M. Othman (Institute of Medico-legal Publications Pvt Ltd, 2021)
In this study, local strains of Lactobacillus plantarum bacteria were isolated from traditional Iraqi rawmilk and milk products. The present study was aimed to study the molecular aspects of Iraqi Lactobacillusplantarum isolates and to evaluate its natural plantaricins antimicrobial activity against pathogenic bacteria. For complete detection for Lactobacillus spp. the partial sequencing of 16S rDNA gene result was analyzedand compared with those in GenBank to find out the different in the sequence using the BLAST program(http:// www. ncbi. nlm.nih). The result was 17 samples diagnosed as Lactobacillus plantarum. Moreover14 isolates of local Lactobacillus plantarum bacteria were show 100% similarity with those previouslyrecorded in GenBank, while 3 isolates were found to display more than 99% similarity with L. plantarumstrains were previously listed in GenBank. Moreover the study also reveals that all L.plantarum strains wasshowed antibacterial activity against three studied indicators bacteria and the plnEF gene (530bp) wasdetected in all 17 isolates of L.plantarum.